Investigating the PS seismic imaging of faults using seismic modelling and data from the Snøhvit field, Barents Sea. Issue 1 (2022) - Cunningham, Jennifer Elizabeth; Weibull, Wiktor Waldemar; Iacopini, Nestor Cardozo and David
No abstract available